Foraging Strategies of Artisanal Fishers in a Brazilian Reservoir. - de Almeida Neto, Miguel Santana; de Almeida, Carolina Alves Collier; Rosa Filho, José Souto; El-Deir, Ana Carla Asfora; da Silva Mourão, José (Human Ecology: An Interdisciplinary Journal, 2018)
Ecological models derived from Optimal Foraging Theory have been used to understand the decision-making processes and optimization of artisanal fisheries. However, many studies do not consider the influence of fishing techniques or seasonality on foraging strategies. We analyzed the optimization strategies and decision-making processes of the fishers at a Brazilian reservoir. Data were collected through interviews and questionnaires involving 65 artisanal fishers, and daily catches were monitored in July/2015 and January/2016. Fishing techniques and seasonality influenced the fishers’ behavior. The fishery activities monitored here were partially or totally consistent with the predictions of the Central-Place Foraging model, but due to the complexity of these activities, other factors also influenced the decision-making of individual fishers. Furthermore, the adoption of strategies that involve “non-ideal” behaviors may be advantageous for the fishers in the context of their individual necessities.